Pathways to breast cancer screening artificial intelligence algorithm validation - Lee, Christoph I.; Houssami, Nehmat; Elmore, Joann G.; Buist, Diana S.M. (Breast (Edinburgh), 2020)
As more artificial intelligence (AI)-enhanced mammography screening tools enter the clinical market, greater focus will be placed on external validation in diverse patient populations. In this viewpoint, we outline lessons learned from prior efforts in this field, the need to validate algorithms on newer screening technologies and diverse patient populations, and conclude by discussing the need for a framework for continuous monitoring and recalibration of these AI tools. Sufficient validation and continuous monitoring of emerging AI tools for breast cancer screening will require greater stakeholder engagement and the creation of shared policies and guidelines.